Immunoexpression of hoxb7 and hoxb9 in salivary gland tumours. (15th March 2016) - Fonseca, Felipe Paiva; Bingle, Lynne; Santos‐Silva, Alan Roger; Lopes, Márcio Ajudarte; Coletta, Ricardo D.; de Andrade, Bruno Augusto Benevenuto; Mariano, Fernanda Viviane; Kowalski, Luiz Paulo; Rangel, Ana Lúcia Carrinho Ayroza; Martins, Manoela Domingues; Meurer, Luise; Hunter, Keith D.; et al.
Abstract : Background: Salivary gland carcinomas are uncommon neoplasms and the identification of new prognostic indicators could improve their management. HOXB7 and HOXB9 are members of the class I homeobox‐containing genes important for normal embryogenesis and that are dysregulated in several human neoplasms. This study investigated HOXB7 and HOXB9 expressions in salivary gland tumourigenesis, their correlation with neoplastic proliferative and angiogenic features and their importance as prognostic markers. Methods: A hundred and fifty salivary gland tumours were organized in tissue microarray and expressions of CD105, Ki67, HOXB7 and HOXB9 were determined through immunohistochemistry. Reactions were quantified and correlated with clinicopathological parameters. Results: In normal glands, HOXB7 was found in basal cells, whereas HOXB9 was seen in serous acinar and scattered ductal cells. Malignancies exhibited an increased vascular density, proliferative index, HOXB7 and HOXB9 expressions when compared with pleomorphic adenoma and Warthin's tumour. Significant correlation was found between HOXB7 and CD105 ( P = 0.004) in adenoid cystic carcinomas, and HOXB7 higher expression significantly correlated with the presence of paresthesia ( P = 0.02). No marker exhibited a significant association with survival rates ( P > 0.05). Conclusion: HOXB7 and HOXB9 were expressed in normal salivary gland and were present in benign and malignant tumours derived from these structures, and HOXB7 significantly correlated with neoangiogenesis in AdCC. These findings suggest that both proteins might play a role in salivary gland tumourigenesis, but they were not significant prognostic determinants in this sample.